Production of Biosurfactant From Pseudomonas Aeruginosa for Micellar Aggregates with Ionic Liquid - Thennarasu, Thamarai (IRC, 2016)
Chemical surfactants used in industry have the adverse environmental effects such as non-degradability property, toxicity and persistence in the environment for a long time. There is a constant search for a cleaner solvent to be a potential substitute to synthetic surfactant that could reduce adverse environmental impact. Rapid advancement in biosciences technology and rising concerns over environmental issues had resulted in the discovery of biosurfactant, which could be a possible alternative to the chemical surfactants.